Conservation Organizations Need to Consider Adaptive Capacity: Why Local Input Matters. Issue 5 (17th December 2015) - Mcleod, Elizabeth; Szuster, Brian; Hinkel, Jochen; Tompkins, Emma L.; Marshall, Nadine; Downing, Thomas; Wongbusarakum, Supin; Patwardhan, Anand; Hamza, Mo; Anderson, Cheryl; Bharwani, Sukaina; Hansen, Lara; et al.
Abstract: Conservation organizations are increasingly applying adaptive capacity assessments in response to escalating climate change impacts. These assessments are essential to identify climate risks to ecosystems, prioritize management interventions, maximize the effectiveness of conservation actions, and ensure conservation resources are allocated appropriately. Despite an extensive literature on the topic, there is little agreement on the most relevant factors needed to support local scale initiatives, and additional guidance is needed to clarify how adaptive capacity should be assessed. This article discusses why adaptive capacity assessment represents a critical tool supporting conservation planning and management. It also evaluates key factors guiding conservation NGOs conducting these assessments in tropical island communities, and explores alternative priorities based on input from academic experts and key local stakeholders. Our results demonstrate that important differences exist between local stakeholders and nonlocal academic experts on key factors affecting adaptation and coping mechanisms. The exclusion of local community input affects the validity of adaptive capacity assessment findings, and has significant implications for the prioritization and effectiveness of conservation strategies and funding allocation.